Natural Language Processing in Higher Education - Putri , Nastiti Susetyo Fanany; Widiharso , Prasetya; Utama, Agung Bella Putra; Shakti, Maharsa Caraka; Ghosh , Urvi (Bulletin of Social Informatics Theory and Application, 2022)
The application of Natural Language Processing (NLP) in an educational institution is still quite broad in its scope of use, including the use of NLP on chatterbots for academic consultations, handling service dissatisfaction, and spam email detection. Meanwhile, other uses that have not been widely used are the combination of NLP and Global Positioning Satellite (GPS) in finding the location of lecture buildings and other facilities in universities. The combination of NLP and GPS is expected to make it easier for new students, as well as visitors from outside the university, to find the targeted building and facilities more effectively.